Hot pants and spandex suits : gender representation in American superhero comic books - De Dauw, Esther (Rutgers University Press, 2021)
The superheroes from DC and Marvel comics are some of the most iconic characters in popular culture today. But how do these figures idealize certain gender roles, body types, sexualities, and racial identities at the expense of others? Hot Pants and Spandex Suits offers a far-reaching look at how masculinity and femininity have been represented in American superhero comics, from the Golden and Silver Ages to the Modern Age. Scholar Esther De Dauw contrasts the bulletproof and musclebound phallic bodies of classic male heroes like Superman, Captain America, and Iron Man with the figures of female counterparts like Wonder Woman and Supergirl, who are drawn as superhumanly flexible and plastic. It also examines the genre's ambivalent treatment of LGBTQ representation, from the presentation of gay male heroes Wiccan and Hulkling as a model minority couple to the troubling association of Batwoman's lesbianism with monstrosity. Finally, it explores the intersection between gender and race through case studies of heroes like Luke Cage, Storm, and Ms. Marvel. Hot Pants and Spandex Suits is a fascinating and thought-provoking consideration of what superhero comics teach us about identity, embodiment, and sexuality.